RETRACTED: Improving the environmental taxation system - Yekimov Sergey; Mohammad Rehabi; Bugay Nadia; Ratynskyi Vadym; Shmorgun Leonid; Ridel T.M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001